The Researches on Vehicle-borne Speed and Direction Detection Method Based on Binocular Image Matching - Gong, Wen Sen; Chen, Jing Ping; Lin, Jun Ji; Zhang, Hui (IOP conference series. Materials Science and Engineering, 2018)
In order to realize accurate perception of vehicle speed and direction, a method for perceiving vehicle speed and direction accurately is proposed, which is based on road surface information images captured by two parallel vehicle-borne imaging devices. The interval time between two imaging devices is controlled accurately, so the overlapping road surface information images can be obtained. The relative motion distance and direction is calculated by image matching. The vehicle speed and direction can be calculated based on the calibration parameters and interval time. The experimental results show that the proposed method has high reliability and accuracy.